Characterization of garlic oil/β-cyclodextrin inclusion complexes and application - Li, Shangjian; Chen, Jiajia; Liu, Yuntong; Qiu, Honghao; Gao, Wei; Che, Kundian; Zhou, Baogang; Liu, Ran; Hu, Wenzhong (Frontiers in Nutrition, 2023)
Garlic oil is a liquid extracted from garlic that has various natural antibacterial and anti-inflammatory properties and is believed to be used to prevent and treat many diseases. However, the main functional components of garlic oil are unstable. Therefore, in this study, encapsulating garlic oil with cyclodextrin using the saturated coprecipitation method can effectively improve its chemical stability and water solubility and reduce its characteristic odor and taste. After preparation, the microcapsules of garlic oil cyclodextrin were characterized, which proved that the encapsulation was successful. Then the concentration of garlic oil cyclodextrin microcapsules was measured the encapsulation rate reached 94.59%, and the product yield reached 90.7%. Finally, the results showed that the encapsulated garlic oil still had antioxidant ability and slow-release properties. The final addition to Plant-based meat gives them a delicious flavor and adds texture and mouthfeel. Provided a new reference for the flavor application of garlic cyclodextrin micro-capsules in plantbased meat patties.